2019
DOI: 10.1038/s41467-019-11856-9
|View full text |Cite
|
Sign up to set email alerts
|

Surpassing the single-atom catalytic activity limit through paired Pt-O-Pt ensemble built from isolated Pt1 atoms

Abstract: Despite the maximized metal dispersion offered by single-atom catalysts, further improvement of intrinsic activity can be hindered by the lack of neighboring metal atoms in these systems. Here we report the use of isolated Pt 1 atoms on ceria as “seeds” to develop a Pt-O-Pt ensemble, which is well-represented by a Pt 8 O 14 model cluster that retains 100% metal dispersion. The Pt atom in the ensemble is 100–1000 times more active than their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
189
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 288 publications
(217 citation statements)
references
References 76 publications
(96 reference statements)
28
189
0
Order By: Relevance
“…The absence of Pd atoms outside HEFO lattice ( Fig. 4a) and around 6.44% surface Pd atoms determined by CO chemisorption (0.0644 μmol CO/μmol Pd, Supplementary Table 1) together indicate that the Pd atoms have been incorporated into both surface and bulk HEFO phase in Pd 1 @HEFO, consistent with the reported phenomena that single platinum-group metal atoms prefer to substitute cerium atoms of CeO 2 rather than adsorb on its surface 28 . To confirm the electronic structure and coordination state of Pd in Pd 1 @HEFO, the X-ray absorption near-edge structure (XANES) and EXAFS measurements are performed at the Pd K-edge.…”
Section: Synthesis and Characterizations As Illustrated Insupporting
confidence: 85%
“…The absence of Pd atoms outside HEFO lattice ( Fig. 4a) and around 6.44% surface Pd atoms determined by CO chemisorption (0.0644 μmol CO/μmol Pd, Supplementary Table 1) together indicate that the Pd atoms have been incorporated into both surface and bulk HEFO phase in Pd 1 @HEFO, consistent with the reported phenomena that single platinum-group metal atoms prefer to substitute cerium atoms of CeO 2 rather than adsorb on its surface 28 . To confirm the electronic structure and coordination state of Pd in Pd 1 @HEFO, the X-ray absorption near-edge structure (XANES) and EXAFS measurements are performed at the Pd K-edge.…”
Section: Synthesis and Characterizations As Illustrated Insupporting
confidence: 85%
“…The size of deposited Pt catalysts in the range of sub-nanometer clusters to single atoms are well controlled by our proposed ALD recipe, which can directly affect the coordination environment of interfacial Pt atoms. The supported Pt single atoms with larger coordination number of Pt-O show lower activity than subnanometric Pt clusters with smaller coordination number of Pt-O 29,30 . Compared with subnanometric Pt clusters on CeO 2 supports, Cu dopants at the interfaces can not only activate the interfacial oxygen, but also weaken the adsorption of CO molecule at interfacial Pt atoms, which are the keys to promoting CO oxidation with lattice oxygen at room temperature in Pt/CeO 2 catalysts 45,46 .…”
Section: Discussionmentioning
confidence: 96%
“…Despite researcher efforts to promote CeO 2 supported Pt single atom catalysts using high temperature steam treatment, heteroatom doping and hydrogen thermal pretreatment, activities of such systems are nonetheless inferior to the activity of state-of-the-art Pt/CeO 2 catalysts with Pt nanocluster sizes in the range of 1.2–1.6 nm 5 , 13 , 16 , 27 , 28 . In order to further improve the atomic efficiency, the highly efficient Pt subnanometric catalysts supported on CeO 2 have been reported, which have shown enhanced low-temperature activity compared with atomically dispersed Pt catalysts 29 , 30 . It has also been reported that the catalytic activity of supported Pt single atoms and sub-nanoclusters is dependent on the dynamically evolving interfacial structures under reaction conditions 31 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Many methods have been developed for synthesizing single‐atom and cluster catalysts, such as mass‐selected soft landing, metal leaching, co‐precipitation, facile adsorption, atomic layer deposition and pyrolysis methods. Among them, the facile adsorption method is very simple and appropriate for practical industrial applications.…”
Section: Introductionmentioning
confidence: 99%